Análise das Teorias Pedagógicas e das Práticas Docentes no Cotidiano do REAJA de Vitória da Conquista - Pimentel, Edna Furukawa (2007)
The objective of this study was to verify the relations between the theories and the pedagogic practices of the teachers that act in the EJA, in the municipal teaching in Vitória da Conquista-BA, oriented by the pedagogic propose of REAJA. .In the attempt of reach this objective, we decide for the quality approach, with the utilization of instruments of interviews partly structures, focal group and observations. As for our systematization, we decide for the elaboration of a descriptive text, as possible as it could, by the dialogue, in the attempt of compare and confront the interviews with the observations, searching to evidence until what point the theory conception of the teachers, interfere and determine their practice in the many circumstances in the classroom. Assuming the pedagogic practice as a unity of analysis, we used the following theory categories: the objective conditions of the teaching work, the development models and the educative praxis. After our survey and analyses of the data, we identify that the forming process (initial and continued), of the form as it s been developed the work, it has not been provided the understanding and the incorporation of the pedagogic theories, because, even existing a variety of conceptions and postures existents in the practices of the teachers, generally, what has predominate it s a formal tendency in their technician and pragmatic versions. However, this instrumental face of the teaching practice, despite of preponderant, it s isn t crystallized, since we identified meaningful practices, that can be thoughtful as a possible alternative in the direction of a emancipate education. This experiences can in the future propitiate concrete actions and collective transformations in repetitive, and imitative practices in creator praxis.